Effects of Plant and Water Level on Nitrogen Variation in Overlying and Pore Water of Agricultural Drainage Ditches in Sanjiang Plain, Northeast China. Issue 4 (30th August 2013) - Zhang, Yan; Zhu, Hui; Yan, Baixing; Li, Xuhui; Ou, Yang
<x xml:space="preserve">Abstract</x> Agricultural drainage ditches are common as temporary storages of drainage water and may improve mitigation capacity of pollutants in Sanjiang Plain. Few ditch management practices have been proposed to alleviate nitrogen loads transported to downstream aquatic systems in this area. This study examined the nitrogen variation in overlying and pore water of a planted and natural drainage ditch of equal size and shape, as well as the low and high water levels of a planted drainage ditch in Sanjiang Plain. Results indicated that longer retention time was in favor of nitrogen removal in overlying water, especially for ammonium nitrogen (NH4‐N); high water level undermined nitrogen removal; there was no significant difference with retention time between the planted drainage ditch and the natural drainage ditch. Conversely, NH4‐N and nitrate nitrogen (NO3‐N) concentrations in pore water were lower in the planted ditch and high water level planted ditch than in the natural ditch. At present, farmers and managers keep drainage ditches nearly full of water to expediently irrigate, which may increase pollutant load in downstream receiving systems. Thus, our study is helpful in guidance for pollution control of agricultural nonpoint source in Sanjiang Plain.